Study of the levels of Arsenic (As) in water for human consumption in the city of Arequipa 2015-2016 - Betty Salazar Pinto (2017)
Cr is one of the most polluting heavy metals that can be found in wastewater from various industries, mainly tanneries; Being Cr (VI) the most toxic known for its carcinogenic character, represents a threat to health and the environment. The objective of this work is to evaluate the contamination by Cr in the Chili River and PIRS in the city of Arequipa, in order to corroborate that the values obtained are within the Maximum Permissible Limits (LMP) and Environmental Quality Standards (ECA) Established by law. A monitoring was carried out fixing four sampling points in the Chili River (Charcani, Puente Tiabaya and Uchumayo) and PIRS, specifically in the affluent of the oxidation lagoon; And the concentrations of Cr were determined by spectrophotometry and voltammetry. The values found for the samples of the Chili River, reveal that the concentrations of Cr do not surpass the ECA. However, for the PIRS affluent the average values of Cr obtained were 4.34; 7.44 and 7.67 mg / L surpassing the LMP of 2.5 mg / L established for surface water effluents from the cement, beer, paper and tannery activities, which represent a permanent environmental contamination.